ANALYSIS OF RECLAMATION COST MODEL IN COAL MINING - PREDERIKA (NIM : 22115006), EVARIA
Direct reclamation cost related to land administration costs are the most important costs that cost around 64 % of the total reclamation costs that are comparable between the other of direct reclamation costs. From the initial analysis carried out, there was a significant difference in unit costs in the land administration activities in the range of Rp. 5,000,000.00 - Rp. 72,000,000.00. In this research, an analysis of land use cost calculation will be carried out which is expected to produce a reclamation cost model that can be used by the government as a guide in evaluating the planned reclamation costs proposed by stakeholders. From the data obtained, clustering is performed to find out the distribution of data to be analyzed using descriptive statistics with box and whisker graphs (box-plot). The difference in the amount of data on reclamation costs in each cluster was caused by the company's inconsistency in placing the amount of reclamation costs per year and also found differences in the stages of reclamation activities in each company. Based on the standard of heavy equipment rental costs issued by the Ministry of PUPR, the results of the calculation analysis found that only about 44.52 % of companies used the standard cost of heavy equipment rental. The model produced in this study is, among others, the cost of land surface arrangement/ha : 𝑓(𝑥)𝑚𝑖𝑛 = (6.41 ÃƒÂ— 𝑡1 )/𝐴 and 𝑓(𝑥)𝑚𝑎𝑥 = (8.74 ÃƒÂ— 𝑡1 )/𝐴, while for the cost of topsoiling/ha : 𝑓(𝑥)𝑚𝑖𝑛 = ((6.41 ÃƒÂ— 𝑡1 ) + (4.48 ÃƒÂ— 𝑡2 ) + (2.59 ÃƒÂ— 𝑡3 ))/𝐴 and 𝑓(𝑥)𝑚𝑎𝑥 = ((8.74 ÃƒÂ— 𝑡1 ) + (6.86 ÃƒÂ— 𝑡2 ) + (3.89 ÃƒÂ— 𝑡3 ))/𝐴, where t1, t2 and t3 = the operation time (hours) for the components of heavy equipment used, A = the area of reclamation land (ha) and 𝑓(𝑥)𝑚𝑖𝑛 and 𝑓(𝑥)𝑚𝑎𝑥 calculated in 105 Rupiah.